2006
DOI: 10.1109/tbme.2006.879473
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Modeling of Bones From CT Data: Sensitivity to Geometry and Material Uncertainties

Abstract: The aim of this paper is to analyze how the uncertainties in modelling the geometry and the material properties of a human bone affect the predictions of a finite-element model derived from computed tomography (CT) data. A sensitivity analysis, based on a Monte Carlo method, was performed using three femur models generated from in vivo CT datasets, each subjected to two different loading conditions. The geometry, the density and the mechanical properties of the bone tissue were considered as random input varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…Although the accuracy of the geometry is the most important factor when simulating wall stress, 26 the wall thickness and the transmural pressure gradient are also very important. Hence, the impact of varying these parameters on wall stress distribution was explored.…”
Section: Exploring Variations Of the Modelmentioning
confidence: 99%
“…Although the accuracy of the geometry is the most important factor when simulating wall stress, 26 the wall thickness and the transmural pressure gradient are also very important. Hence, the impact of varying these parameters on wall stress distribution was explored.…”
Section: Exploring Variations Of the Modelmentioning
confidence: 99%
“…image-based finite element analysis modeling has been studied previously. 38,39 It has been demonstrated that the coefficients of variation of the output variables from finite element analysis modeling never exceed 9%. Further improvement in CT image resolution and automatic image processing techniques will certainly reduce the uncertainties in the patientspecific modeling in the future.…”
Section: Et Al Shoulder Stress and Aneurysm Growthmentioning
confidence: 99%
“…Laz et al included uncertainty in the density-to-modulus and density-to-strength relationships used in assigning bone material properties and predicted large amounts of variability in stress and risk in a proximal femur [35]. Monte Carlo and Latin hypercube approaches were implemented by Taddei et al to evaluate the impact of uncertainty in geometry, density, and material properties of the bone tissue on bone displacement stresses and strains under compression and torsion loading [36]. Using correlation coefficients, the study reported that scaling of the geometry had the greatest impact on the performance measures.…”
Section: Structural Reliabilitymentioning
confidence: 99%